2021
DOI: 10.1253/circrep.cr-21-0018
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Cardiac Rehabilitation in Japan Between 2010 and 2017 ― An Epidemiological Survey ―

Abstract: Background: Despite the prognostic effectiveness of cardiac rehabilitation (CR) in patients with cardiovascular disease (CVD), it has been underutilized. Understanding the trend of dissemination of CR over the years would help provide a perspective of CR in Japan. Methods and Results:A retrospective epidemiological survey between fiscal years 2010 and 2017 was conducted using the diagnosis procedure combination database (a Japanese administrative database). Data on 2,046,302 patients with CVD from 1,632 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…Although the number of patients who underwent CR, the total number of CR sessions, and the number of facilities providing CR increased from 2013 to 2017, the participation rate for outpatient CR was lower than that of inpatient CR. The lower participation in outpatient CR was consistent with the findings of another study in Japan; 26 however, the prior study did not suggest methods to address this.…”
Section: Lower Outpatient Cr Participationsupporting
confidence: 83%
“…Although the number of patients who underwent CR, the total number of CR sessions, and the number of facilities providing CR increased from 2013 to 2017, the participation rate for outpatient CR was lower than that of inpatient CR. The lower participation in outpatient CR was consistent with the findings of another study in Japan; 26 however, the prior study did not suggest methods to address this.…”
Section: Lower Outpatient Cr Participationsupporting
confidence: 83%
“…The results of this study indicated that the implementation rate of CR after device implantation in Japan was 23% ( n = 16 445), and the implementation rate of CR after device implantation in patients with comorbid heart failure was only 32% ( n = 9262). It was reported that the implementation rates of CR after myocardial infarction, heart failure, and cardiac surgery in Japan were 66%, 47%, and 77%, respectively 11 . The implementation rate of CR after device implantation was low compared to these rates.…”
Section: Discussionmentioning
confidence: 97%
“…In Japan, inpatient cardiac rehabilitation has become standard care for patients hospitalized for CVD. In 2017, the implementation rates for inpatient cardiac rehabilitation were 76.5%, 65.6%, and 46.9% for patients hospitalized for cardiac surgery, acute coronary syndrome, and heart failure, respectively [ 19 ], which constitute the main population of this study. Health insurance is mandatory in Japan, and cardiac rehabilitation is covered by the Japanese health care system.…”
Section: Methodsmentioning
confidence: 99%